AS IMPERFEIÇÕES DO CRIME DA MALA: "CINE-GÊNEROS" E REENCARNAÇÕES NO CINEMA DOS PRIMÓRDIOS - SOUZA, JOSÉ INACIO DE MELO (Revista USP, 2000)
AS IMPERFEIÇÕES DO CRIME DA MALA: "CINE-GÊNEROS" E REENCARNAÇÕES NO CINEMA DOS PRIMÓRDIOS.